cis-acting mutations that affect rop protein control of plasmid copy number. - Moser, D R (1984)
A number of pMB1 derivatives provide a trans-acting function that can suppress lethal runaway replication of a temperature-sensitive copy-number mutant of NTP1. Deletion analysis indicates that the region of the pMB1 genome that contains the rop gene is required for this suppression. Mutant derivatives of the temperature-sensitive copy-number mutant plasmid whose conditional lethal phenotype is not suppressed in trans by the region encoding the rop gene have been isolated. These rop-insensitive derivatives contain single nucleotide changes within the RNA I coding region.